Strategies For Improving Coordination Between The Public and Private Institutions For Agricultural and Rural Development - Kaman Nainggolan (Forum penelitian Agro Ekonomi, 2002)
EnglishAgriculture/agribusiness plays a strategic role in labor absorption, capital formation, foreign exchange, providing food supply, and supply a market for domestically produced industrial goods. Globalization has suddenly changed the way leaders of nations in managing agriculture/agribusiness development. Many countries are more open, moving toward democracy. Through the impact of decentralization, the government is shifting from dominating development in the past to people participation. This implies that the private sector will play a more active role in agriculture/agribusiness and rural development. With the new vision, agriculture should not be seen as a separate sector (on-farm), but in a more broad way which is agribusiness consisting of all related activities from upstream to downstream agribusiness subsystem. Good governance is a prerequisite to encourage private institutions to participate in agriculture/agribusiness and rural development. Policy measures to improve coordination between public and private institutions includes: infrastructure development, development of seed industry, develop and strengthen agro-industry in rural areas, develop and strengthen market information, market restructuring and trade policy, development of the private sector, micro, small, and medium size enterprises, macroeconomic stability, land market deregulation, strengthening of governance, environment sustainability, and improving rural productivity. All of these measures must be transparent and communicated to all stakeholders in agriculture/agribusiness and rural development. IndonesianSektor pertanian memiliki peranan yang strategis dalam penyerapan tenaga kerja, pembentukan kapital, penyediaan pangan, dan menyadiakan bahan baku untuk industri dalam negeri. Globalisasi secara serta merta talah merubah kebijakan pemimpin-pemimpin nasional dalam menangani pembangunan pertanian dan agribisnis. Berbagai negara menjadi lebih terbuka menuju ke arah demokrasi. Melalui dampak desentralisasi, pemerintah telah beralih dari sikap mendominasi di masa lalu menuju pada partisipasi masyarakat. Hal ini berimplikasi kepada semakin besarnya peran sektor swasta dalam pembangunan pertanian di pedesaan. Dengan visi baru ini, maka pertanian tidak lagi di pandang sebagai sektor yang terpisah-pisah, namun menjadi lebih luas, dimana mencakup aktivitas-aktivitas yang terkaIt mulai dari subsistem hulu sampai hilir. Pemerintahan yang baik dituntut untuk mendorong koordinasi antara institusi swasta dan publik mencakup: pengembangan infrastruktur, pengembangan industri benih, pengembangan dan penguatan agroindustri di pedesaan, pengembangan informasi pasar, merestruktur pasar dan kebijakan perdagangan, pengembangan sektor swasta, usaha mikro, kecil, menengah, stabilitas ekonomi makro, deregulasi pasar lahan, penguatan pemerintahan, keberlanjutan lingkungan, dan peningkatan produktivitas pedesan. Semua kebijakan ini mestilah dilakukan secara transparan dan dikomunikasikan kepada stakeholders yang terlibat dalam pembangunan pertanian dan pedesaan.